Perbaikan Model Kebergunaan Pada Aplikasi Perangkat Bergerak Dengan Menambahkan Atribut Gejala Buruk - Cahya Bagus Sanjaya; Daniel Siahaan (Informatics Engineering Department-UWKS, 2015)
Usability is a very important aspect and one of the key factors for the successful mobile application. Usability is an attribute to define the quality of user interface and the quality of interaction between user and application. Models to measure the usability of desktop application can not directly be used for mobile applications because of the differences between the characteristics of desktop applications and mobile applications. Previous research developed a model to measure usability on a mobile application. Somehow, it lacks recommendations for new user interface usability evaluation of the mobile application that is being measured and there is no weighting for each attribute. This study combines qualitative primary data taken from questionnaires and quantitative secondary data taken from the activity logs application (Bad Symptoms) when user run mobile application. Weighting for each attribute is done by an expert of mobile applications. Analytical Hierarchy Process (AHP) Method is used to analyze experimental data. Result from this research is a novel model to measure usability for mobile application that have a weight to each usability attributes and provides recommendation for improvement of existing user interfaces.